Fotografia e formação de si: memória, narrativa e docência - Lismar Antônio Alves Santos Vilela (2018)
This article tells the historical background of a teacher from his childhood with his father artist, the photographic machine inherited, the experience with professional photography and his training as a teacher / artist and his eternal curiosity with photography, analyzes the results of work done with a photograph with elementary and middle school students from the State School Boa Vista in the city of Contagem / MG in the year 2017. Students who had an opportunity to discover photography and its history, and use it as an expressive medium representing the school and their social spaces, their social and affective relations, the nature that surrounds them, etc. Shoot the school, beyond the usual, show that students have creative potential with an object of habitual use the camera.